2010
DOI: 10.1007/s11142-010-9133-4
|View full text |Cite
|
Sign up to set email alerts
|

Conditional conservatism and cost of capital

Abstract: Forthcoming in Review of Accounting Studies* We are grateful to Alon Brav for providing access to the ex ante cost of equity capital estimates, and to Dan Segal for his assistance in computing the CR conservatism proxy. We also appreciate the comments and suggestions from Gauri Bhat, Peter Electronic copy available at: http://ssrn.com/abstract=1544307 Conditional Conservatism and Cost of Capital ABSTRACTWe empirically test the association between conditional conservatism and cost of equity capital.Conditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(84 citation statements)
references
References 67 publications
(92 reference statements)
5
78
1
Order By: Relevance
“…It is also supported by the results of (Khalifa & Ben Othman, 2015;Zare et al,. 2013;Lara et al, 2011;Gietzmann & Trombetta, 2003). Thus, this result leads to the rejection of the first main null hypothesis in this study.…”
Section: Results Of Main Research Hypotheses Testsupporting
confidence: 63%
See 1 more Smart Citation
“…It is also supported by the results of (Khalifa & Ben Othman, 2015;Zare et al,. 2013;Lara et al, 2011;Gietzmann & Trombetta, 2003). Thus, this result leads to the rejection of the first main null hypothesis in this study.…”
Section: Results Of Main Research Hypotheses Testsupporting
confidence: 63%
“…Regarding conservatism, results indicated lack of compliance with accounting conservatism during preparing the financial statements. (Lara, Osma, & Penalva, 2011) investigated the relationship between conditional conservatism and firm's cost of equity capital by using asset-pricing test to study whether more conditionally conservative firms gain lower expected returns and by analyzed the relation between conditional conservatism and implied cost of capital as a proxy to estimate the cost of equity capital. The outcomes of their study showed that there is a significant adverse relationship between conditional conservatism and the cost of equity capital.…”
Section: Introductionmentioning
confidence: 99%
“…In the same vein, a set of studies showed that conservatism benefits to debt contracting (Zhang, 2008;Nikolaev, 2009). Besides this contracting effect, other works support that accounting conservatism enhances firm value by mitigating information asymmetry and constraining earnings managements (LaFond and Roychowdhury, 2008;LaFond and Watts, 2008;Francis and Martin, 2010;García Lara et al, 2011;Ettredge et al, 2012;Kim and Zhang, 2013). Other studies explore the implications of capital market with regard to conservative accounting, especially the impact of conservatism on the cost of equity capital.…”
Section: Introductionmentioning
confidence: 97%
“…Many studies reveal that not only conservatism is still an accounting practice that defeated other accounting principles, but its degree has increased over the last 30 years (Givoly and Hayn, 2000;Giner and Rees, 2001;Grambovas et al, 2006). García Lara et al (2011) argue that this omnipresence may be attributed to the potential beneficial effects of conservatism for all the stakeholders of the firm.…”
Section: Introductionmentioning
confidence: 99%
“…An impressive amount of literature has analysed how the information reported compulsorily in the fi nancial statements should be to reduce the problems created by information asymmetries. One example of this literature is the large stream of studies about whether accounting numbers should be more or less conservative (LaFond & Watts, 2008, García Lara, García Osma & Penalva, 2011. Similarly, there are many studies analysing whether and how voluntary disclosure contributes to reduce adverse selection problems.…”
Section: Discussionmentioning
confidence: 99%